2018
DOI: 10.4103/jisp.jisp_18_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of hemodynamic, vasoconstrictive, and SpO2variability during different stages of periodontal surgery performed using 0.5% ropivacaine or 2% lignocaine HCl (1:80,000 adrenaline) local anesthesia: A randomized, double-blind, split-mouth pilot study

Abstract: Aim:The aim of this study is to compare anesthetic, hemodynamic, vasoconstrictive, and SpO2 variability of 0.5% ropivacaine to the “gold standard” lignocaine (2%) with epinephrine (1:80,000) during periodontal surgery.Materials and Methods:A total of 20 systemically healthy controls meeting the inclusion criteria were selected from the Outpatient Department of Sri Sai College of Dental Surgery. Preoperatively, all participants were infiltrated with 0.5 ml of 0.5% ropivacaine intradermally as test solution to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The above study also supports our result that peri-tonsillar infiltration of ropivacaine with adrenaline is effective in reducing intraoperative bleeding. 16 A crucial result of our study was the decreased bleeding observed with ropivacaine peritonsillar infiltration when compared to the control group. Hence, we recommend the use of peri-tonsillar infiltration of ropivacaine (0.75%) in view of better management of intra-operative blood loss…”
Section: Discussionmentioning
confidence: 65%
“…The above study also supports our result that peri-tonsillar infiltration of ropivacaine with adrenaline is effective in reducing intraoperative bleeding. 16 A crucial result of our study was the decreased bleeding observed with ropivacaine peritonsillar infiltration when compared to the control group. Hence, we recommend the use of peri-tonsillar infiltration of ropivacaine (0.75%) in view of better management of intra-operative blood loss…”
Section: Discussionmentioning
confidence: 65%
“…In studies by Reddy et al [ 4 ] and Mishra et al [ 11 ], the perioperative changes in heart rate and blood pressure were insignificant. Bansal et al [ 14 ] noted no statistically significant difference in the mean systolic and diastolic pressure values pre- and postoperatively 45 min after administration of 0.75% ropivacaine and 2% lignocaine with adrenaline, while the mean systolic blood pressure was increased in the ropivacaine and lignocaine groups.…”
Section: Discussionmentioning
confidence: 99%
“…After its commercial release, ropivacaine has been extensively used for perioperative pain relief in the medical field, with consistently better outcomes than other local anesthetic agents [ 4 ]. Its use in the dental discipline has expanded to studies on periodontic procedures to evaluate its anesthetic efficacy [ 11 ], topical anesthesia of the oral mucosa [ 12 ], simple extraction procedures [ 3 13 14 ], lower third molar surgeries[ 1 4 5 15 16 17 18 19 ], surgical removal of the upper third molars[ 20 ], surgical removal of chronic periapical lesions [ 21 ], oral aphthosis [ 22 ], mandibular osteotomy [ 23 ], and postoperative pain control after elective cleft palate repair in children [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vasodilation results in the increased rate of absorption and reduced duration of action of anesthesia and consequently, increased anesthetic blood level and risk for toxicity. [ 9 10 11 ] Prilocaine is classified as the weakest powerful vasodilator. So, it can be useful for anesthetizing the patients who are prohibited from the use of local anesthetics with adrenaline.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] Felypressin is similar to oxytocin, and it can induce oxytocic action on the uterus. [ 10 12 ] Felypressin can also cause coronary artery vasoconstriction. So, felypressin is contraindicated in the late pregnancy stages and in patients with unstable angina and poorly controlled hemorrhage.…”
Section: Introductionmentioning
confidence: 99%